Flourishing as an ecological self: why our relationships with nonhuman nature matter - Aguilar, Tony, author; Shockley, Ken, advisor; McShane, Katie, committee member; Walker, Sarah, committee member (Colorado State University. Libraries, 2024)
Writers in environmental ethics are often concerned, and reasonably so, with articulating what it is about beings in nonhuman nature that hold value. In doing so, however, whether our human relationships to nonhuman nature are valuable is a question that is often overlooked. This project aims to address that question and argues that our relationships to nonhuman nature are crucial to our flourishing, and because of this, they ought to be central in our discussion of value in the nonhuman natural world. I take particular kinds of relations to constitute relationships and advance three particular relations–care, reciprocity and respect–as relations that together constitute ideal human relationships with the more than human world. Given a clear picture of what a good relationship with the nonhuman natural world looks like, we can begin repairing our relationship to nature for the betterment of ourselves and the rest of the natural world.
Keywords: ecological self; relational value; ecofeminism; sense of place; environmental ethics